Landscape of m6A RNA methylation regulators in liver cancer and its therapeutic implications - Zhao, Jindu; Li, Guo-Ying; Lu, Xian-Ying; Zhu, Li-Ran; Gao, Qun (Frontiers in Pharmacology, 2024)
Liver cancer remains as the third leading cause of cancer-related death globally as of 2020. Despite the significant progress made in the field of liver cancer treatment, there is still a lack of effective therapies in patients with advanced cancer and the molecular mechanisms underlying liver cancer progression remain largely elusive. N6-methyladenosine (m 6 A) modification, as the most prevalent and abundant internal RNA modification in eukaryotic RNAs, plays an essential role in regulating RNA metabolism including RNA splicing, stability, translation, degradation. To date, there is mounting evidence showing that m 6 A dysregulation is closely associated with the onset and development of many tumors including hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC) and hepatoblastoma (HB). In this review, we summarize the last research progress regarding the functions of m 6 A-related regulators in liver cancer and its underlying mechanisms. Additionally, we also discuss the therapeutic applications of m 6 A-based inhibitors in liver cancer treatment.